Radiologic Update on Arthroplasties in the Wrist and Hand - Petscavage-Thomas, Jonelle M.; Gustas-French, Cristy; Walker, Eric A. (Seminars in Musculoskeletal Radiology, 2019)
Arthritis involving the hand and wrist can significantly impair functions of daily living. Although arthrodesis provides pain relief, it limits range of motion at the affected joint. Arthroplasty is an alternative surgical treatment for hand and wrist arthritis, providing both pain relief and restoration of a range of motion. Over the past decade, several advances have occurred in hand and wrist arthroplasty designs. This article reviews component design, normal imaging appearance, and common complications of arthroplasty used in the wrist and hand. It also introduces readers to newer arthroplasty designs.
Keywords: wrist; arthroplasty; distal radioulnar joint; ligament reconstruction tendon interposition; suspensionplasty